How effective are automatic stabilisers? Theory and empirical results for Germany and other OECD countries - Karl-Heinz Tödter; Michael Scharnagl (Deutsche Bundesbank, 2004)
Cyclically induced changes in taxes and government expenditures which tend to stabilise aggregate output are called automatic stabilisers. Using a small macro model, this paper reviews alternative methods of measuring the smoothing power of automatic stabilisers and discusses their relationship to the Ricardian Equivalence Theorem. Based on simulation exercises with the macroeconometric multi-country model of the Deutsche Bundesbank, the empirical part of the paper presents estimates of the smoothing power of automatic stabilisers for Germany and some other OECD countries. The results for Germany suggest that in the first year 15 to 20 per cent of an exogenous demand shock are absorbed by the automatic stabilisers. Similar results are obtained for France, Italy, the Netherlands, UK, Canada and the US.
Keywords: H62; H30; E62; 330; Fiscal policy; automatic stabilisers; smoothing power; compensation method; Finanzpolitik; Eingebauter Stabilisator; Ricardianisches Äquivalenztheorem; Ökonometrisches Makromodell; Simulation; Deutschland; OECD-Staaten